The impact of affirmative action on the gendered: Occupational segregation in South Africa - Stephan Klasen; Anna Minasyan (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
This paper studies the impact of an affirmative action policy on occupational segregation by gender in South Africa. We estimate the effects of the Employment Equity Act of 1998, the Black Economic Empowerment Act in 2003 and the Codes of Good Conduct in 2007 on (Black) female employment in top occupations using individual level, repeated cross-section data of 21 years. The findings based on difference-in-difference-in-difference identification strategy show that the probability of Black female employment in top occupations increased after 2003, however it decreased after 2007. Overall, the effects are quite small. We offer several explanations for our findings.
Keywords: J7; J16; J15; J18; 330; affirmative action; occupational segregation; gender; South Africa